ANALISA KINERJA KEUANGAN PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA, MALAYSIA DAN THAILAND MENGGUNAKAN ANALISIS RASIO DAN RISK BASED CAPITAL - NGATIMIN NGATIMIN (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2018)
AbstractTo measure financial performance analysis using ratio analysis in accordance with PSAK 28 which consists of Underwriting Ratio, Loss Ratio, Commission Expense Ratio, Liability to Liquid Asset Ratio, Investment to Technical Reserve Ratio, Net Premium Growth, Own Retention Ratio. Parameter used in Indonesia is Risk Based Capital (RBC) in accordance with Decree of Minister of Finance No. 424 / KMK.06 / 2003. The results of the ratio analysis based on the report of annual report are Underwriting Ratio of Indonesia 24.09%, Malaysia 13.70% and Thailand 12.22%, Loss Ratio Indonesia 44.44%, Malaysia 55.99% and Thailand 60.05% Malaysian Revenue Commission 11.53%, Indonesia 11.99% and Thailand 19.40%, Malaysia Liquidity Ratio 83.45%, Indonesia 55.96% and Thailand 54.42%, Investments to Technical Ratio of Indonesia 685.36% , Thailand 318.18% and Malaysia 93.65%, Net Premium Growth Ratio Indonesia 21.56%, Malaysia 13.29% and Thailand 4.42% and Own Retention Ratio Thailand 851.72%, Malaysia 79.14% and Indonesia 72.12%. While his Risk Base Capital analysis is Thailand 907.58%, Malaysia 920.68% and Indonesia 415.07 Keywords: Financial Statement, Ratio Analysis, Risk Based Capital